Qualitative study exploring lessons from Liberia and the UK for building a people-centred resilient health systems response to COVID-19. Issue 8 (1st August 2022) - McCollum, Rosalind; Zaizay, Zeela; Dean, Laura; Watson, Victoria; Frith, Lucy; Alhassan, Yussif; Kollie, Karsor; Piotrowski, Helen; Bates, Imelda; Anderson de Cuevas, Rachel; Harris, Rebecca; Chowdhury, Shahreen; et al.
Abstract : Introduction: COVID-19 has tested the resilience of health systems globally and exposed existing strengths and weaknesses. We sought to understand health systems COVID-19 adaptations and decision making in Liberia and Merseyside, UK. Methods: We used a people-centred approach to carry out qualitative interviews with 24 health decision-makers at national and county level in Liberia and 42 actors at county and hospital level in the UK (Merseyside). We explored health systems' decision-making processes and capacity to adapt and continue essential service delivery in response to COVID-19 in both contexts. Results: Study respondents in Liberia and Merseyside had similar experiences in responding to COVID-19, despite significant differences in health systems context, and there is an opportunity for multidirectional learning between the global south and north. The need for early preparedness; strong community engagement; clear communication within the health system and health service delivery adaptations for essential health services emerged strongly in both settings. We found the Foreign, Commonwealth and Development Office (FCDO) principles to have value as a framework for reviewing health systems changes, across settings, in response to a shock such as a pandemic. In addition to the eight original principles, we expanded to include two additional principles: (1) the need for functional structures and mechanisms for preparation and (2) adaptable governance and leadership structures to facilitate timely decision making and response coordination. We find the use of a people-centred approach also has value to prompt policy-makers to consider the acceptance of service adaptations by patients and health workers, and to continue the provision of 'routine services' for individuals during health systems shocks. Conclusion: Our study highlights the importance of a people-centred approach, placing the person at the centre of the health system, and value in applying and adapting the FCDO principles across diverse settings.